New pedagogic challenges in engineering education and the answer of IGIP - M. . Auer; D. . Dobrovska; A. . Edwards; E. . Lickl (Высшее образование в России)
The paper describes the approach of International Society of Engineering Education (IGIP) to new pedagogic challenges in engineering education in the XXI century. The main tendencies for the education development and requirements to the future of learning are given. The change of the social role of the engineering education is stressed, and the new questions of theengineering education are listed.